A METHOD OF STUDYING RESPIRATION - Osterhout, W. J. V. (The Rockefeller University Press, 1918)
An apparatus is described which makes it possible to measure rapidly and accurately small amounts of CO(2) given off by organisms of all kinds. The apparatus can also be used to measure photosynthesis.